Knockdown of ST6Gal-I increases cisplatin sensitivity in cervical cancer cells. Issue 1 (December 2016) - Zhang, Xiaopeng; Pan, Chunchen; Zhou, Lei; Cai, Zhaogen; Zhao, Shufang; Yu, Donghong
Abstract Background Sialyltransferase I (ST6Gal-I) is an enzyme involved in tumor metastasis that processes sialic acid precursors into their mature form, enabling them to regulate gene expression. However, the effect of ST6Gal-I on the biological behavior of cancer cells remain unclear. This study was the first to demonstrate the influence of ST6Gal-I on cisplatin sensitivity in cervical cancer cells. Methods Knockdown of ST6Gal-I was performed by shRNA and HeLa cells combination with cisplatin were tested. Results We showed that down-regulation of ST6Gal-I promoted cell apoptosis and inhibited proliferation and invasion in cervical cancer cells. Knockdown of ST6Gal-I by RNA interference increased the sensitivity of HeLa cells to cisplatin in vitro, and reduced tumor volume and suppressed subcutaneous tumor growth in response to cisplatin treatment in a xenograft mouse model in vivo. Conclusions The results provide new information that ST6Gal-I plays an important role in several biological or pathological processes including drug resistance in cervical cancer and may be a potential therapeutic target to improve the response to chemotherapy in cervical cancer patients.